A salt-resistant fracturing thickening agent and a preparation method thereof

CN122978359APending Publication Date: 2026-10-27PUYANG GREEN SINGULARITY NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611311183.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这些固态残渣会堵塞支撑剂孔隙,加剧储层渗透率损伤,进而对油气返排效率产生不利影响

Benefits of technology

1、改性聚乙烯醇(PVA)纤维表面携带聚合乙烯基,在后续反相乳液自由基聚合体系中:纤维表面的碳碳双键能够与体系内AM、AMPS、ACMO单体发生自由基共聚。最终实现:PVA纤维通过共价化学键锚固在稠化剂高分子三维网络之中,由单纯物理掺杂转变为化学接枝复合结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978359A_ABST
    Figure CN122978359A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of thickener technology. This invention provides a thickener for salt fracturing and its preparation method. The method comprises the following steps: S1, weighing 220g of acrylamide, 50g of 2-acrylamide-2-methylpropanesulfonic acid, 20g of acryloylmorpholine, 20g of modified polyvinyl alcohol fiber, and 2g of 2wt% ammonium persulfate, adding them to 300g of distilled water, dissolving them, and adjusting the pH to 7±0.1 to obtain an aqueous phase; S2, under stirring, injecting the aqueous phase into 310-320g of oil phase to obtain an emulsion; S3, pouring the emulsion into a three-necked flask, stirring, and purging with nitrogen for 45min to start the reaction; during the reaction, adding 2g of 1wt% sodium bisulfite to the three-necked flask; the temperature is 40±1℃, and the reaction is carried out for 4-5h to obtain a copolymer; S4, adding a phase-inverting agent to the copolymer to obtain the final product. This invention introduces polyvinyl alcohol (PVA) fiber to ensure excellent temperature resistance of the prepared thickener while reducing its delamination residue content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thickener technology, specifically relating to a thickener for salt fracturing and its preparation method. Background Technology

[0002] In the continuous vertical exploration and development of oil and gas fields, high-temperature deep well reservoirs place stringent demands on the temperature resistance of fracturing fluids. Due to its outstanding performance in thickening and rheology, polyacrylamide (PAM) has become a core material for fracturing fluid applications. Currently, high-temperature resistant fracturing fluids mostly rely on a mixture of powder-based thickeners and crosslinking agents. However, the application range is limited by factors such as the poor solubility of powder-based thickeners, the need for advance preparation before construction, and the high cost of crosslinking agents. In contrast, emulsion-based thickeners, with their rapid dissolution and simple preparation process, meet the needs of large-scale continuous mixing in the field, and therefore have gained wider application.

[0003] To create fracturing fluids that possess both easy solubility and excellent temperature, salt, and shear resistance, existing technologies employ copolymerization of acrylamide (AM), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), and acryloylmorpholine (ACMO), and introduce polyvinyl alcohol fibers. Using a reverse emulsion polymerization process, a novel polyacrylamide copolymer p(AM / AMPS / ACMO), serving as a thickener, has been successfully synthesized. This polyvinyl alcohol fiber-modified p(AM / AMPS / ACMO) thickener exhibits excellent temperature and shear resistance.

[0004] When testing the debonding performance of this thickener, ammonium sulfate was selected as the debonding agent. "Easy debonding" refers to the breakage of polyacrylamide molecular chains under the action of a debonding agent, achieving a viscosity reduction effect. However, due to the ordered molecular chain arrangement and high crystallinity of crystalline polyvinyl alcohol (PVA) fibers, sulfate radicals have difficulty penetrating deep into the fiber interior, and conventional oxidative debonding agents have limited degradation effects on them. During this process, although the large molecules of the AM / AMPS / ACMO copolymer can degrade into small molecule fragments, reducing the system viscosity, undegraded crystalline polyvinyl alcohol (PVA) fibers remain as solid residues in the fractures. These solid residues clog the proppant pores, exacerbating reservoir permeability damage and consequently adversely affecting oil and gas flowback efficiency. Summary of the Invention

[0005] To address the problems existing in the background art, the present invention provides a thickener for salt fracturing and its preparation method. By introducing polyvinyl alcohol (PVA) fibers, the thickener is guaranteed to have excellent temperature resistance while reducing its debonding residue content.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a thickener for salt fracturing includes the following steps: S1. Weigh 10g of Span-80 and 5g of Tween-60 into a beaker, add 300g of white oil and stir to mix evenly to obtain the oil phase; weigh 220g of acrylamide AM, 50g of 2-acrylamide-2-methylpropanesulfonic acid AMPS, 20g of acryloylmorpholine ACMO, 20g of modified polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate and pour into 300g of distilled water, stir to dissolve completely, and adjust the pH to 7±0.1 to obtain the aqueous phase; S2. After the aqueous phase temperature drops to room temperature, the aqueous phase obtained in S1 is injected into 310-320g of oil phase under high-speed stirring, and stirred thoroughly to obtain an emulsion. S3. Pour the emulsion obtained in S2 into a three-necked flask, and start the reaction by purging nitrogen gas for 45 minutes while stirring. During the reaction, add 2g of 1wt% sodium bisulfite in batches to the three-necked flask. Under nitrogen protection, the temperature is 40±1℃, and the reaction is carried out for 4 to 5 hours to obtain the copolymer. S4. Add a phase inversion agent to the copolymer obtained in S3 to obtain the thickener for salt fracturing.

[0007] Furthermore, the oil phase comprises white oil and emulsifier, and the mass ratio of the two is 20:(0.9-1.1).

[0008] Furthermore, the emulsifiers include Span-80 and Tween-60, and the mass ratio of the two is 2:1.

[0009] Furthermore, in S1, the pH is adjusted using 50 mL of a 4 mol / L sodium hydroxide aqueous solution.

[0010] Furthermore, in S4, the phase inversion agent is Tween-80, and the dosage is 37-39g.

[0011] Furthermore, the modified polyvinyl alcohol fiber is prepared as follows: A1. Add 1.1g of polyvinyl alcohol (PVA) and 20mL of dimethyl sulfoxide to a three-necked flask, soak, and heat to 50±1℃ with stirring to dissolve, to obtain the first mixture; A2. Add a few drops of concentrated sulfuric acid as a catalyst, add 2 mL of acryloyl chloride, and reflux at 50°C until the solution becomes gel-like to obtain the reaction solution; A3. Pour the reaction solution obtained in A2 into a beaker containing water, precipitate out, filter, wash, and dry in a vacuum drying oven to obtain the modified polyvinyl alcohol fiber.

[0012] Furthermore, in A1, the soaking time is 0.5-0.7 hours.

[0013] Furthermore, in A3, the drying temperature is 50±2℃, and the drying time is 12-14h.

[0014] A thickener for salt fracturing is prepared using the method described above.

[0015] This application has the following beneficial effects: 1. Modified polyvinyl alcohol (PVA) fibers carry polymerized vinyl groups on their surface. In the subsequent reverse emulsion free radical polymerization system, the carbon-carbon double bonds on the fiber surface can undergo free radical copolymerization with AM, AMPS, and ACMO monomers within the system. Ultimately, the PVA fibers are anchored within the three-dimensional network of the thickener polymer through covalent chemical bonds, transforming from a simple physical doping structure into a chemically grafted composite structure.

[0016] 2. Covalent bonds replace the original hydrogen bonds and physical entanglement, greatly enhancing the interfacial bonding force between PVA fibers and the copolymer matrix; under high temperature, high mineralization, and continuous shear conditions, the fibers are not easily slipped or peeled off from the polymer network, and the dense network structure can be stably retained; ACMO provides steric hindrance and AMPS provides anionic salt-resistant groups, which, together with the continuous composite network constructed by grafted fibers, prevent the polymer chains from curling up under the action of salt ions, continuously maintaining the thickening ability, and retaining the original advantages of temperature resistance and shear resistance.

[0017] 3. The covalent linkage sites enable free radicals to continuously transfer to the PVA fiber phase and simultaneously attack the PVA molecular backbone; the secondary hydroxyl groups on the PVA molecular chain are easily oxidized and broken by sulfate free radicals, and the originally complete long fibers are fragmented along with the polymer network; the ester bonds formed by grafting can be hydrolyzed in the hot water environment of depolymerization, which helps to break down the PVA macromolecules and form water-soluble small molecule oxidized fragments, significantly reducing the residue content. Attached Figure Description

[0018] Figure 1 This is a comparison chart of the temperature and shear resistance test data of the thickener samples prepared in Examples 1-3 and Comparative Example 1 of the present invention.

[0019] Figure 2 This is a comparison chart of the test data of the thickener samples prepared in Examples 1-3 and Comparative Example 1 of the present invention, showing the content of the broken glue residue. Detailed Implementation

[0020] The present application will be further described in detail below with reference to the embodiments.

[0021] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.

[0022] Example 1 (1) The preparation method of modified polyvinyl alcohol fiber is as follows: A1. Add 1.1g of polyvinyl alcohol (PVA) and 20mL of dimethyl sulfoxide to a three-necked flask, soak for 0.6h, and heat to 50℃ with stirring to dissolve it, thus obtaining the first mixture.

[0023] A2. Add two drops of concentrated sulfuric acid as a catalyst, then add 2 mL of acryloyl chloride. Reflux at 50°C until the solution becomes gel-like to obtain the reaction solution.

[0024] A3. Pour the reaction solution obtained in A2 into a beaker containing water, precipitate out, filter, wash, and dry in a vacuum drying oven at 50℃ for 13 hours to obtain modified polyvinyl alcohol fiber.

[0025] The polyvinyl alcohol (Nanshi brand, 1750±50 / 1788, 99% content) was purchased from Nanjing Chemical Reagent Co., Ltd.

[0026] (2) A method for preparing a thickener for salt fracturing, comprising the following steps: S1. Weigh 10g of Span-80 and 5g of Tween-60 into a beaker, add 300g of white oil and stir to mix evenly to obtain the oil phase; weigh 220g of acrylamide AM, 50g of 2-acrylamide-2-methylpropanesulfonic acid AMPS, 20g of acryloylmorpholine ACMO, 20g of modified polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate and pour into 300g of distilled water, stir to dissolve completely, add 50mL of 4mol / L sodium hydroxide aqueous solution to adjust the pH to 7 to obtain the aqueous phase.

[0027] The oil phase consists of white oil and emulsifiers in a mass ratio of 20:1. The emulsifiers consist of Span-80 and Tween-60 in a mass ratio of 2:1.

[0028] S2. After the aqueous phase temperature drops to room temperature, the aqueous phase obtained in S1 is injected into 315g of oil phase under high-speed stirring, and stirred thoroughly to obtain an emulsion.

[0029] S3. Pour the emulsion obtained in S2 into a three-necked flask, and start the reaction by purging nitrogen gas for 45 minutes while stirring. During the reaction, add 2g of 1wt% sodium bisulfite to the three-necked flask in batches. Under nitrogen protection, the temperature is 40℃, and the reaction is carried out for 4.5 hours to obtain the copolymer.

[0030] S4. Add 38g of phase inversion agent Tween-80 to the copolymer obtained in S3 to obtain a thickener for salt fracturing.

[0031] Example 2 A method for preparing a thickener for salt fracturing includes the following steps: S1. Weigh 10g of Span-80 and 5g of Tween-60 into a beaker, add 300g of white oil and stir to mix evenly to obtain the oil phase; weigh 220g of acrylamide AM, 50g of 2-acrylamide-2-methylpropanesulfonic acid AMPS, 20g of acryloylmorpholine ACMO, 20g of modified polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate and pour into 300g of distilled water, stir to dissolve completely, add 50mL of 4mol / L sodium hydroxide aqueous solution to adjust the pH to 7 to obtain the aqueous phase.

[0032] The oil phase consists of white oil and emulsifiers in a mass ratio of 20:0.9. The emulsifiers consist of Span-80 and Tween-60 in a mass ratio of 2:1.

[0033] S2. After the aqueous phase temperature drops to room temperature, the aqueous phase obtained in S1 is injected into 310g of oil phase under high-speed stirring, and stirred thoroughly to obtain an emulsion.

[0034] S3. Pour the emulsion obtained in S2 into a three-necked flask, and start the reaction by purging nitrogen gas for 45 minutes while stirring. During the reaction, add 2g of 1wt% sodium bisulfite to the three-necked flask in batches. Under nitrogen protection, the temperature is 40℃, and the reaction is carried out for 4.5 hours to obtain the copolymer.

[0035] S4. Add 37g of phase inversion agent Tween-80 to the copolymer obtained in S3 to obtain a thickener for salt fracturing.

[0036] Example 3 A method for preparing a thickener for salt fracturing includes the following steps: S1. Weigh 10g of Span-80 and 5g of Tween-60 into a beaker, add 300g of white oil and stir to mix evenly to obtain the oil phase; weigh 220g of acrylamide AM, 50g of 2-acrylamide-2-methylpropanesulfonic acid AMPS, 20g of acryloylmorpholine ACMO, 20g of modified polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate and pour into 300g of distilled water, stir to dissolve completely, add 50mL of 4mol / L sodium hydroxide aqueous solution to adjust the pH to 7 to obtain the aqueous phase.

[0037] The oil phase consists of white oil and emulsifiers in a mass ratio of 20:1.1. The emulsifiers consist of Span-80 and Tween-60 in a mass ratio of 2:1.

[0038] S2. After the aqueous phase temperature drops to room temperature, the aqueous phase obtained in S1 is injected into 320g of oil phase under high-speed stirring, and stirred thoroughly to obtain an emulsion.

[0039] S3. Pour the emulsion obtained in S2 into a three-necked flask, and start the reaction by purging nitrogen gas for 45 minutes while stirring. During the reaction, add 2g of 1wt% sodium bisulfite to the three-necked flask in batches. Under nitrogen protection, the temperature is 40℃, and the reaction is carried out for 4.5 hours to obtain the copolymer.

[0040] S4. Add 39g of phase inversion agent Tween-80 to the copolymer obtained in S3 to obtain a thickener for salt fracturing.

[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that in the preparation of the thickener for salt fracturing, the modified polyvinyl alcohol fiber is replaced with polyvinyl alcohol fiber.

[0042] Specifically, a method for preparing a thickener for salt fracturing includes the following steps: S1. Weigh 10g of Span-80 and 5g of Tween-60 into a beaker, add 300g of white oil and stir to mix evenly to obtain the oil phase; weigh 220g of acrylamide AM, 50g of 2-acrylamide-2-methylpropanesulfonic acid AMPS, 20g of acryloylmorpholine ACMO, 20g of polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate and pour into 300g of distilled water, stir to dissolve completely, add 50mL of 4mol / L sodium hydroxide aqueous solution to adjust the pH to 7 to obtain the aqueous phase.

[0043] The oil phase consists of white oil and emulsifiers in a mass ratio of 20:1. The emulsifiers consist of Span-80 and Tween-60 in a mass ratio of 2:1.

[0044] S2. After the aqueous phase temperature drops to room temperature, the aqueous phase obtained in S1 is injected into 315g of oil phase under high-speed stirring, and stirred thoroughly to obtain an emulsion.

[0045] S3. Pour the emulsion obtained in S2 into a three-necked flask, and start the reaction by purging nitrogen gas for 45 minutes while stirring. During the reaction, add 2g of 1wt% sodium bisulfite to the three-necked flask in batches. Under nitrogen protection, the temperature is 40℃, and the reaction is carried out for 4.5 hours to obtain the copolymer.

[0046] S4. Add 38g of phase inversion agent Tween-80 to the copolymer obtained in S3 to obtain a thickener for salt fracturing.

[0047] Test case Test subjects: Thickener samples prepared in Examples 1-3 and Comparative Example 1.

[0048] Test items and methods: ① Temperature and shear resistance test: Each thickener sample was prepared into a 1wt% solution using water. The temperature was gradually increased from 20℃ to 100℃. Multiple test points were set (20℃, 40℃, 60℃, 80℃, 100℃). A rotational rheometer was used to measure the shear rate at each test point at 170s. -1 After shearing for 10 minutes, the viscosity was tested.

[0049] ② Test of gel breaking residue content: Prepare gel samples (0.4wt% thickener sample, 0.3wt% crosslinking agent), add ammonium persulfate as a gel breaking agent at 0.65g / L, and break the gel at 90℃ for 3h. Then test the gel breaking residue content.

[0050] Experimental results: see Figure 1 and Figure 2 .

[0051] Results analysis: Combining Figure 1 and Figure 2 Analysis of Examples 1-3 and Comparative Example 1 shows that in the preparation of the thickener for salt fracturing, replacing the polyvinyl alcohol fiber with the modified polyvinyl alcohol fiber prepared in this invention does not significantly affect the excellent temperature and shear resistance of the thickener, while significantly reducing its debonding residue content.

[0052] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0053] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A method for preparing a thickener for salt-resistant fracturing, characterized in that, Includes the following steps: S1. Weigh 220g of acrylamide, 50g of 2-acrylamide-2-methylpropanesulfonic acid, 20g of acryloylmorpholine, 20g of modified polyvinyl alcohol fiber and 2g of 2wt% ammonium persulfate, pour them into 300g of distilled water, stir to dissolve completely, and adjust the pH to 7±0.1 to obtain the aqueous phase. S2. Under stirring, inject the aqueous phase obtained in S1 into 310-320g of the oil phase to obtain an emulsion; S3. Pour the emulsion obtained in S2 into a three-necked flask, stir, and purge with nitrogen for 45 minutes to start the reaction; add 2g of 1wt% sodium bisulfite during the reaction; react at 40±1℃ for 4~5h to obtain the copolymer; S4. Add a phase inversion agent to the copolymer obtained in S3 to obtain the thickener for salt fracturing.

2. The method for preparing the thickener for salt-resistant fracturing according to claim 1, characterized in that, The oil phase comprises white oil and emulsifier, and the mass ratio of the two is 20:(0.9-1.1).

3. The method for preparing the thickener for salt-resistant fracturing according to claim 2, characterized in that, The emulsifiers include Span-80 and Tween-60, and the mass ratio of the two is 2:

1.

4. The method for preparing the thickener for salt-resistant fracturing according to claim 1, characterized in that, In S1, the pH was adjusted using a 4 mol / L sodium hydroxide aqueous solution.

5. The method for preparing the thickener for salt fracturing according to claim 1, characterized in that, In S4, the phase inversion agent is Tween-80, and the dosage is 37-39g.

6. The method for preparing the thickener for salt-resistant fracturing according to claim 1, characterized in that, The modified polyvinyl alcohol fiber is prepared as follows: A1. Add 1.1g of polyvinyl alcohol and 20mL of dimethyl sulfoxide to a three-necked flask, soak, and heat to 50±1℃ with stirring to obtain the first mixture; A2. Add a few drops of concentrated sulfuric acid, then add 2 mL of acryloyl chloride, and reflux until it becomes a gel to obtain the reaction solution; A3. Pour the reaction solution obtained in A2 into a beaker containing water, precipitate out, filter, wash, and dry to obtain the modified polyvinyl alcohol fiber.

7. The method for preparing the thickener for salt fracturing according to claim 6, characterized in that, In A1, the soaking time is 0.5-0.7 hours.

8. The method for preparing the thickener for salt fracturing according to claim 6, characterized in that, In A3, the drying temperature is 50±2℃ and the drying time is 12-14h.

9. A thickener for salt-resistant fracturing, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.